Analisis Gramatikal Teks Cantakaparwa - Puspitorini, Dwi; Mastuti, Woro Retno (Makara Human Behavior Studies in Asia, 2002)
Cantakaparwa Manuscripts (CP) written on palm-leaves are prose texts in old Javanese. These texts considered unique and interesting because they contain the famous story of Sutasoma and the language used in it is the combination of old and modern Javanese. These are the main reason why the grammatical aspects of CP texts become the focus of this research. This research, which is still in its early stage, chose verbs as the focus of the analysis. The reason is that verbs dominantly function as predicate, and predicate is the most important part of a sentence. There are two topics that will be focused on, i.e. (a) what are the forms of polymorpheme verbs in CP texts?, (b) what are the structure of sentences with verbal predicates in CP texts? The method used in this research is a synchronic language method, which is also known as a descriptive method. This method is considered in accordance with the objective of this research because it tries to fi nd out a language that exists at a certain time. The results of the research show that there are some combinations of old and modern Javanese grammatical aspects in CP texts. Most affi xes that function as verb formers in modern Javanese are the same as those in old Javanese. However, the forms that can only be found in modern Javanese began to appear. The sentence patterns with Predicate + Subject in old Javanese are usually marked by particles of emphasis, but they are rarely found in CP texts.